Response of Micronutrient on Ber Fruit Quality During Storage in cv. Banarasi Karaka under Ambient Condition - Singh, Vikas Kumar; Shanker, Karuna; Tiwari, N. K.; Rao, O. P. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted to find out the effect of micronutrient on ber fruit quality during storage in cv. Banarasi Karaka under ambient condition, laid out at main experiment station department of horticulture, Narendra Deva University of Agriculture and Technology Kumarganj, Faizabad (U.P.) during the years 2008−2009. Plants received uniform cultural operations throughout the experimental period. Treatments included control, ferrous sulphate (FeSO4) @ 0.3%, ferrous sulphate @ 0.6%, potassium sulphate (K2SO4) @ 1.0%, potassium sulphate @ 2.0%, borax (Na2B4O7 10H2O) @ 0.5%, borax @ 1.0%, FeSO4 @ 0.3%+K2SO4 @ 1.0%+borax @ 0.5%, FeSO4 @ 0.6%)+K2SO4 @ 2.0%)+Borax @ 1.0%. The nutrients were sprayed as aqueous solutions using Tween-20 as a surfactant. First spray was done in month of September just before flowering and second spray was done after fruit setting. The result were found that the fruit quality with respect of highest TSS. sugar, ascorbic acid, lowest acidity was obtained with spray of FeSO4 @ 0.6%+K2SO4 @ 2.0%+borax @ 1.0% followed by treatment and consisting 0.3% ferrous sulphate+1.0% potassium sulphate+0.5% borax and FeSO4 @ 0.6%. While minimum physiological weigh loss was recorded (6.53%) with the treatment FeSO4 @ 2.0%+borax 1.0%+K2SO4 @ 2.0% followed by treatment borax @ 1.0%, minimum decay loss recorded 8.83% with the treatment borax @ 0.5% followed by treatment, FeSO4 @ 0.3%+K2SO4 @ 1.0%+borax @ 0.5%.